Effects of Cholinesterase Inhibitor Medication on QTc Interval in Memory Clinic Patients - Isotalo, Hanna Karita; Lehtovaara, Joanna Karoliina; Ekblad, Laura Linnea; Nuotio, Maria Susanna; Langén; Ville Lauri Johannes (SAGE PUBLICATIONS INC, 2025)
Background: Cholinesterase inhibitors (ChEIs)-donepezil, rivastigmine, and galantamine-are beneficial in treating Alzheimer disease (AD). However, due to their impact on extra-cerebral acetylcholine signaling, concerns about cardiac adverse effects, including QT interval prolongation, persist. Despite this, evidence-based guidelines for electrocardiogram (ECG) monitoring during ChEI treatment are lacking, and prior studies on ChEIs and corrected QT intervals (QTc) yield inconsistent findings.
Objective: This study aimed to investigate the association between ChEI use and changes in QTc intervals among older adults.
Methods: We collected retrospective data from first-time visitors to the geriatric memory clinic of Turku City Hospital in 2017 and 2019. We included patients who were newly prescribed ChEIs and had ECG data available (n = 126, mean age 81.1 years, 56.3% female). QTc prolongation was defined as >= 460 ms in females and >= 450 ms in men. Paired t tests compared QTc means before and during ChEI use, and McNemar tests analyzed changes in the proportion of prolonged QTc.
Results: Mean +/- SD QTc (ms) before versus during ChEI use was: 420.8 +/- 24.0 versus 423.9 +/- 28.0 (P = .13) for donepezil; 416.0 +/- 20.4 versus 416.5 +/- 26.1 (P = .92) for galantamine; 416.1 +/- 22.3 versus 409.6 +/- 20.1 (P = .30) for rivastigmine; and 419.7 +/- 23.4 versus 421.5 +/- 27.3 (P = .34) for all ChEIs. Prolonged QTc occurred in 7.9% of patients before versus 12.7% during ChEI use (P = .21).
Conclusion and Relevance: We found no statistically significant association between ChEI use and QTc interval prolongation or an increased proportion of pathological QTc values during ChEI treatment. Larger studies are warranted to establish evidence-based recommendations on ECG monitoring during ChEI medication.